UNDERSTANDING THE CONSTRAINTS AND - Cudjoe, Korlekour Rosina (My University, 2011)
Private sector-led development has become widely adopted by donors and development agencies who have designed programmes to address market failures impeding the growth of ‘pro-poor’ enterprises. At the same time, high value agricultural products have been identified as a particular area of value chain opportunities for enterprises based in low income communities. This research report critically assesses the constraints on such a development approach through an in-depth case study of Marula Natural Products (MNP). MNP has received substantial donor support over the past ten years to support the processing and marketing of marula-based products. The main findings are that, despite this support, MNP has not met expectations because of significant challenges including poor institutional arrangements, inadequate and inconsistent management attention, absence of entrepreneurial drive/risk-taking and a mindset of donor dependency. These issues identified in the case study are relevant for the review and improvement of such donor programmes if communities are to be enabled to participate more effectively in international value chains.
MM - P&DM
Keywords: Sustainable development; Marula Natural Products; Donor funding